Simulated gastrointestinal pH condition improves antioxidant properties of wheat and rice flours - Chan, Kim Wei; Khong, Nicholas Mun Hoe; Iqbal, Shahid; Ismail, Maznah (MDPI, 2012)
The present study was conducted to evaluate the antioxidant properties of wheat and rice flours under simulated gastrointestinal pH condition. After subjecting the wheat and rice flour slurries to simulated gastrointestinal pH condition, both slurries were centrifuged to obtain the crude phenolic extracts for further analyses. Extraction yield, total contents of phenolic and flavonoids were determined as such (untreated) and under simulated gastrointestinal pH condition (treated). 1,1-diphenyl-2-picrylhydrazyl radical (DPPH•) scavenging activity, 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) radical cation (ABTS•+) scavenging activity, ferric reducing antioxidant power (FRAP), beta-carotene bleaching (BCB) and iron chelating activity assays were employed for the determination of antioxidant activity of the tested samples. In almost all of the assays performed, significant improvements in antioxidant properties (p < 0.05) were observed in both flours after treatment, suggesting that wheat and rice flours contain considerably heavy amounts of bound phenolics, and that their antioxidant properties might be improved under gastrointestinal digestive conditions.